The Judge as Tragic Hero: An Arendtian Critique of Judging - Berkowitz, Roger (HannahArendt.net, 2008)
I am interested in exploring why some judges rhetorically portray themselves as tragic heroes who are bound by the law when others, both dissenting judges and respected legal observers, argue that the law is unsettled.